Gated SPAD Arrays for Single-Photon Time-Resolved Imaging and Spectroscopy - Enrico Conca; Iris Cusini; Fabio Severini; Rudi Lussana; Franco Zappa; Federica Villa (IEEE Photonics Journal, 2019)
In this paper, we present the architecture and the experimental characterization of an improved version of a previously developed 32 × 32 Single Photon Avalanche Diodes (SPADs) and Time to Digital Converters (TDCs) array, and two new arrays (with 8 × 8 and 128 × 1 pixels) with the additional capability of actively gating the detectors with sub-nanosecond rise time. The arrays include high performance SPADs (0.04 cps/μm2, 50% peak PDE) and provide down to 410 ps Full-Width at Half-Maximum (FWHM) single shot precision and excellent linearity. We developed a camera to exploit these imagers in time-resolved, single-photon applications.